Gwaabaw: Applying Anishinaabe Harvesting Protocols to Energy Governance - Awasis, Sakihitowin (Canadian Geographies / Géographies canadiennes, 2020)
Oil and gas extraction has transformed Anishinaabe society in ways that undermine the consensual, holistic, and egalitarian basis of natural law. To many Indigenous people, framing fossil fuels and other energy sources as “natural resources” does not accurately define energy projects or capture related risks. Some Anishinaabe pipeline opponents have suggested that traditional harvesting protocols–culturally embedded moral precepts that govern the gathering of food and medicinal plants–also be applied to activities that produce energy. This paper explores how this could be done, focusing on tar sands extraction and the Line 3 expansion plan. I begin by discussing Anishinaabe harvesting protocols, identifying four overlapping key concepts: rights, responsibility, relationality, and reciprocity. These principles are then mapped onto Anishinaabe understandings of oil, hydro, wind, and solar energy. The resulting analysis challenges extractivist narratives of energy production, opening possibilities to rethink the relationship between people and energy as well as the values that inform energy decisions.